Pemodelan AHP Dan AHP-SAW Dalam Menentukan Mahasiswa Terbaik Fakultas Ilmu Keperawatan Universitas Muhammadiyah Kalimantan Timur - Highness Mailani Putri; Hamada Zein; Sri Mar’ati Sholikhah; Azelina Zahra Riadini; Seftiani Nur; Lilis Sagita; Ridha Anisa Soldzu Parnga (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The best students are students who have excellence both in values and ethics. In the graduation ceremony every year, the selection of the best students is a reward and also as a motivation that will be a supporting material for a student to plunge into a wider layer of society. In determining the best students at the Faculty of Nursing, Muhammadiyah University of East Kalimantan, it is still done manually using Microsoft excel. So it is necessary to implement a computer-based information system that can support decision making by considering the criteria to be assessed. AHP and AHP-SAW methods are used in modeling this decision support system and comparing the two methods. The AHP-SAW method produces better results than the AHP method. This is because the AHP-SAW combined method combines the best of both methods.